2020
DOI: 10.1080/03007995.2020.1853510
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged prothrombin time as an early prognostic indicator of severe acute respiratory distress syndrome in patients with COVID-19 related pneumonia

Abstract: Background: Clinical observations demonstrated that COVID-19 related pneumonia is often accompanied by hematological and coagulation abnormalities including lymphopenia, thrombocytopenia, and prolonged prothrombin time. The evaluation of laboratory findings including coagulation and inflammation parameters may represent a promising approach for early determination of COVID-19 severity. Methods and Materials s: In the present study, we aimed to identify laboratory parameters present upon admission in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
(22 reference statements)
0
11
2
1
Order By: Relevance
“…Furthermore, on a study conducted on 233 patients, Baranovskii et al [ 26 ] found that prothrombin measured upon admission was prolonged in COVID-19 patients that were further transferred to ICU (82 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, on a study conducted on 233 patients, Baranovskii et al [ 26 ] found that prothrombin measured upon admission was prolonged in COVID-19 patients that were further transferred to ICU (82 patients).…”
Section: Discussionmentioning
confidence: 99%
“…in another study, no relationship was found between prothrombin time, activated partial thromboplastin time and disease severity [ 83 ]. However, prothrombin time and C-reactive protein levels were high in ICU COVID-19 patients and they can be used as a biomarker to severity of the disease [ 84 ]. In addition, other coagulation abnormalities such as low antithrombin III, associated with a high risk of thromboembolic events [ 85 ].…”
Section: Coagulation Parametersmentioning
confidence: 99%
“…90 Baranovskii et al found significantly prolonged admission PT in ICU-transferred patients compared with stable COVID-19 patients. 91 Such findings may be due to systemic inflammation-related coagulopathy rather than reduced hepatic function.…”
Section: Hepatic Manifestations In Covid-19mentioning
confidence: 99%